2016
DOI: 10.1016/j.polymertesting.2015.11.017
|View full text |Cite
|
Sign up to set email alerts
|

Tension behaviour of HNBR and FKM elastomers for a wide range of temperatures

Abstract: This article presents uniaxial tension tests of three different elastomer compounds commonly applied as seal materials in the oil and gas industry. The tests were performed at five different temperatures, ranging from −20 to 150 • C. Optical measurements were used to ensure high quality stress-strain data. The material samples were exposed to a cyclic deformation history, enabling the viscoelastic behaviour to be explored. A considerable effect of temperature changes was found, with a pronounced increase of st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 20 publications
0
19
0
Order By: Relevance
“…It is therefore essential to obtain precise 23 data at large deformations from experiments in order to 24 analyse such complex load cases successfully. 25 Several studies have been conducted addressing the 26 performance of polymeric materials at elevated tem- with cameras for subsequent DIC analysis, is that such 57 materials are susceptible to volume change during plas-58 tic deformation. Hence, the transverse strains have to 59 be measured in order to calculate the true stress.…”
mentioning
confidence: 99%
“…It is therefore essential to obtain precise 23 data at large deformations from experiments in order to 24 analyse such complex load cases successfully. 25 Several studies have been conducted addressing the 26 performance of polymeric materials at elevated tem- with cameras for subsequent DIC analysis, is that such 57 materials are susceptible to volume change during plas-58 tic deformation. Hence, the transverse strains have to 59 be measured in order to calculate the true stress.…”
mentioning
confidence: 99%
“…For the creep test, only a slight volume increase can be observed. As the deviatoric behaviour of the material has been found to be viscous and cycle dependent [4] the deformation in this stage is likely to be dominated by the hydrostatic stresses, meaning that the measured axial stress dened in Equation 5 yields a good approximation to the hydrostatic stress response of the tested materials. In the following results, the measured axial stress is therefore denoted as the hydrostatic stress.…”
Section: Resultsmentioning
confidence: 99%
“…Constitutive models commonly applied to predict the visco-hyperelastic response of elastomers in nite element simulations assume a nearly isochoric behaviour independent of loading mode [1,2,3]. Based on available experimental data in uniaxial tension (UT) [4] and conned axial compression (CAC) [5], there are clear indications that this approach can be inaccurate for certain elastomers. It appears that the materials can exhibit a considerable increase of volume in UT, £ arne.ilseng@ntnu.no while the response in CAC is much stier with respect to volume change, yet there is a nite bulk modulus also in this loading case.…”
Section: Introductionmentioning
confidence: 99%
“…43.5 MPa at TR = 0.25, whereas the leg with no groove showed a gradual increase, with its highest value of 32.5 MPa at TR = 1.50. Using the stress-strain curve suggested in the literature [25], the approximate stress of the 40%-deformed FKM material was experimentally reported to be about 1.5-2.0 MPa at constant volume assumption. Referring to the suggested equations in another literature [1], it was reported that when elastomeric seals were compressed by 40%, the contact pressure of the axially and radially restrained grooves would exponentially increase by about 20-25 times greater than those of the unrestrained geometry.…”
Section: Contact Pressure and Gap Distance Under Axial Compressionmentioning
confidence: 99%